Exosomes: Vehicles for the Transfer of Toxic Proteins Associated with Neurodegenerative Diseases? - Bellingham, Shayne A.; Guo, Belinda; Coleman, Bradley; Hill, Andrew F. (Frontiers in Physiology, 2012)
Exosomes are small membranous vesicles secreted by a number of cell types including neurons and can be isolated from conditioned cell media or bodily fluids such as urine and plasma. Exosome biogenesis involves the inward budding of endosomes to form multivesicular bodies (MVB). When fused with the plasma membrane, the MVB releases the vesicles into the extracellular environment as exosomes. Proposed functions of these vesicles include roles in cell-cell signaling, removal of unwanted proteins, and the transfer of pathogens between cells. One such pathogen which exploits this pathway is the prion, the infectious particle responsible for the transmissible neurodegenerative diseases such as Creutzfeldt-Jakob disease (CJD) of humans or bovine spongiform encephalopathy (BSE) of cattle. Similarly, exosomes are also involved in the processing of the amyloid precursor protein (APP) which is associated with Alzheimer's disease (AD). Exosomes have been shown to contain full-length APP and several distinct proteolytically cleaved products of APP, including Aβ. In addition, these fragments can be modulated using inhibitors of the proteases involved in APP cleavage. These observations provide further evidence for a novel pathway in which PrP and APP fragments are released from cells. Other proteins such as superoxide dismutase I (SOD-1) and alpha-synuclein (involved in Amyotrophic Lateral Sclerosis (ALS) and Parkinson’s disease respectively) are also found associated with exosomes. This review will focus on the role of exosomes in neurodegenerative disorders and discuss the potential of these vesicles for the spread of neurotoxicity, therapeutics and diagnostics for these diseases.